O tripé do Instituto Butantan para evitar a extinção da jararacailhoa - Marques, Otávio A. V.; Monteiro, Paulo H. N.; Almeida Santos, Selma M. (Herpetologia Brasileira, 2026)
The Golden Lancehead, endemic to Queimada Grande Island and critically endangered, requires swift, integrated action. We present the Butantan Institute’s tripod to prevent extinction: research, ex situ conservation, and education. In the research axis, we are consolidating studies and approaches in natural history, behavioral ecology, reproductive physiology, genetics, and microbiota, providing baselines for management, pairings, and assisted-reproduction protocols. For ex situ conservation, the Laboratório de Ecologia e Evolução (LEEv) at Instituto Butantan is developing a vivarium designed to replicate, as far as feasible, the island’s Atlantic Forest structure and microclimate, promoting ecological and behavioral health, reducing inbreeding, and building a stock suitable for future reintroductions. In education, initiatives within LEEv facilities and in coastal schools engage teachers, students, and the public through participatory science, strengthening social support and curbing illegal trade. Integrating these axes offers a replicable framework for other Brazilian snakes and increases the species’ population viability.